Bone grafting for scaphoid nonunion surgery: a systematic review and meta-analysis. (1st May 2022) - Duncumb, Joseph W.; Robinson, Patrick G.; Williamson, Tom R.; Murray, Iain R.; Campbell, Doug; Molyneux, Samuel G.; Duckworth, Andrew D.
Abstract : Aims: The purpose of this systematic review was to determine the rates of union for vascularized versus non-vascularized grafting techniques in the operative management of scaphoid nonunion. Secondary aims were to determine the effect of the fixation techniques used, the source of grafting, as well as the influence of fracture location (proximal pole) and avascular necrosis (AVN). Methods: A search of PubMed, MEDLINE, and Embase was performed in June 2021 using the Preferred Reporting Items for Systematic Review and Meta-Analyses statement and registered using the PROSPERO International prospective register of systematic reviews. The primary outcome was union rate. Results: There were 78 studies that met the inclusion criteria with a total of 7, 671 patients (87.8% male, 12.2% female). The mean age was 27.9 years (SD 3.8) and the mean follow-up was 30.9 months (SD 25.9). The mean union rate was 88.7% (95% confidence interval (CI) 85.0 to 92.5) for non-vascularized grafts versus 87.5% (95% CI 82.8 to 92.2) for vascularized grafts (p = 0.685). Pooled analysis of trial data alone found a mean union rate of 82.4% (95% CI 66.9% to 97.9%) for non-vascularized grafts and 89.4% (95% CI 84.1% to 94.7%) for vascularized grafts (p = 0.780). No significant difference was observed in union rates between any of the fixation techniques used in the studies (p = 0.502). Distal radius and iliac crest graft source had comparable mean union rates (86.9% (95% CI 83.1 to 90.7) vs 87.6% (95% CI 82.2 to 92.9); p = 0.841). Studies that excluded patients with both proximal pole fractures and AVN (n = 14) had a mean union rate of 96.5% (95% CI 94.2 to 98.9) that was significantly greater than the mean union rate of 86.8% (95% CI 83.2 to 90.4) observed in the remaining studies (p < 0.001). Conclusion: Current evidence suggests vascularized bone grafting does not yield significantly superior results to non-vascularized grafting in scaphoid nonunion management. However, potential selection bias lessens the certainty of these findings. The fixation type or source of the graft used was not found to influence union rates either. Sufficiently designed and powered prospective randomized controlled trials in this area are needed. Cite this article: Bone Joint J  2022;104-B(5):549–558.